2023
DOI: 10.1212/wnl.0000000000207113
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between CSF Markers of Inflammation, White Matter Lesions, and Cognitive Decline in Individuals Without Dementia

Abstract: Backgroundand ObjectivesSmall vessel disease (SVD) and neuroinflammation both occur in Alzheimer’s disease (AD), and other neurodegenerative diseases. It is unclear if these processes are related or independent mechanisms in AD, especially in the early stages of disease. We therefore investigated the association between white matter lesions (WML; the most common manifestation of SVD), and CSF biomarkers of neuroinflammation and their effects on cognition in a population without dementia.MethodsIndividuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
18
1
Order By: Relevance
“…Previous studies showed that inflammation is significantly associated with white matter dysfunction before [ 78 ] and during VCI [ 79 ], suggesting that inflammation plays an early important role in the etiology of white matter dysfunction [ 80 ]. Indeed, the NLRP3 and AIM2 inflammasomes were found to be activated in the brains of BCAS-operated mice [ 47 , 81 ], but it remained unclear whether modulating the activity of their common mediator caspase-1 may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that inflammation is significantly associated with white matter dysfunction before [ 78 ] and during VCI [ 79 ], suggesting that inflammation plays an early important role in the etiology of white matter dysfunction [ 80 ]. Indeed, the NLRP3 and AIM2 inflammasomes were found to be activated in the brains of BCAS-operated mice [ 47 , 81 ], but it remained unclear whether modulating the activity of their common mediator caspase-1 may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that increased levels of plasma PLGF indicated increased white matter lesions, regardless of cognitive status or Aβ presence. 88 It is thought that PLGF could not only serve as a sensitive and specific biomarker of cerebrovascular injury but also provide us with mechanistic avenues to explore for VCID. This is being explored by several groups currently.…”
Section: A Deep Dive Into 3 Current Promising Biomarkers Plgf-candida...mentioning
confidence: 99%
“…Another study also showed that increased levels of plasma PLGF indicated increased white matter lesions, regardless of cognitive status or Aβ presence. 88…”
Section: A Deep Dive Into 3 Current Promising Biomarkersmentioning
confidence: 99%
“…Outside of cSLE, prior work has revealed that inflammatory states are associated with cognitive dysfunction and depressed mood. 10 Therefore, bidirectional interactions between disease activity or inflammatory status with neurocognitive deficits or potent emotional states should be expected in cSLE. Although a greater genetic susceptibility may independently yield an overall more progressive disease status in cSLE versus adult-onset SLE patient populations, what remains largely unclear are the neuropathological mechanisms associated with more severe presentation of neuropsychiatric symptoms and the poorer long-term prognosis in patients with cSLE.…”
Section: Neuropsychiatric Symptoms In Patients With Csle With and Wit...mentioning
confidence: 99%
“…Outside of cSLE, prior work has revealed that inflammatory states are associated with cognitive dysfunction and depressed mood 10 . Therefore, bidirectional interactions between disease activity or inflammatory status with neurocognitive deficits or potent emotional states should be expected in cSLE.…”
Section: Introductionmentioning
confidence: 99%